THE INFLUENCE OF TATO, DAR, CR ON ROA IN FOOD AND BEVERAGE COMPANIES - Widjayanti, Indriyani; Aslamiyah, Suaibatul (Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine the effect of Total Assets Turnover, Debt to Asset Ratio, Current Ratio to Return On Asset. By using the food and beverage companies as population, and technically the sample in this study used purposive sampling, namely 13 companies. The sources used in this study were obtained on the BEI website. The results showed that Total Assets Turnover (TATO) had a negative and insignificant effect on Return On Assets (ROA), Debt ro Asset Ratio (DAR) had a negative and significant effect on Return On Asset (ROA), and Current Ratio (CR) had a positive and significant effect on Return On Asset (ROA)